2018
DOI: 10.3390/en11082010
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Based Energy Management Algorithm for Smart Energy Buildings

Abstract: A smart grid facilitates more effective energy management of an electrical grid system. Because both energy consumption and associated building operation costs are increasing rapidly around the world, the need for flexible and cost-effective management of the energy used by buildings in a smart grid environment is increasing. In this paper, we consider an energy management system for a smart energy building connected to an external grid (utility) as well as distributed energy resources including a renewable en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 24 publications
0
99
0
Order By: Relevance
“…It was found that the proposed approach provided near optimum performance when compared to a theoretically optimal benchmark. In 2018, Kim and Lim utilized Q learning to learn when to charge and discharge a battery and when to buy and sell from the grid [100]. The authors report significant energy cost savings when compared to other methods.…”
Section: Smart Homes and The Electrical Gridmentioning
confidence: 99%
“…It was found that the proposed approach provided near optimum performance when compared to a theoretically optimal benchmark. In 2018, Kim and Lim utilized Q learning to learn when to charge and discharge a battery and when to buy and sell from the grid [100]. The authors report significant energy cost savings when compared to other methods.…”
Section: Smart Homes and The Electrical Gridmentioning
confidence: 99%
“…Finally, it is claimed that the environmental inertia must be deeply analysed in order to understand the time response of the environment and correctly compute its effect in the learning analysis. Concerning the energy efficiency of next generation buildings, the papers of Yang et al [45] and Kim and Lim [46] give details on how the power consumption can be reduced utilising the Q-learning algorithm. Both papers provide details on how the state space is constructed and employ a stochastic framework for the problem formulation.…”
Section: Applications Of Reinforced Learning To Energy Systemsmentioning
confidence: 99%
“…For instance, Brida et al [18] developed a battery energy management strategy for a MG by using the batch RL technology. Sunyong et al [19] proposed a RL-based EMS for a MG-like smart building to reduce the operating cost. Ganesh et al [20] proposed an evolutionary adaptive dynamic programming and RL framework for dynamic energy management of a smart MG. Elham et al [21] designed a multiagent-based RL system for optimal distributed energy management in a MG.…”
Section: Introductionmentioning
confidence: 99%